Aortic Stenosis Current Perspectives - Magnusson, Peter (IntechOpen, 2019)
As the most common cardiac valve disease, aortic stenosis is frequently encountered by healthcare providers in clinical practice. It may be suspected from a cardiac murmur found at a routine clinical exam, signs on ECG, heart failure, or an episode of syncope or arrhythmia. Echocardiography as well as other imaging tools provide information about the degree of severity of the stenosis. Nevertheless, careful judgement of potential symptoms is crucial. When it comes to treatment, a catheter-based approach has emerged as the preferred option in many cases, even though open-chest surgery is still standard treatment. Regardless of treatment modality, a multidisciplinary team is needed to provide optimal management of patients with aortic stenosis. This book provides all the necessary information on aortic stenosis, including etiology, diagnosis, treatment, and follow-up.